2017
DOI: 10.1371/journal.pmed.1002279
|View full text |Cite
|
Sign up to set email alerts
|

Fresh fruit consumption in relation to incident diabetes and diabetic vascular complications: A 7-y prospective study of 0.5 million Chinese adults

Abstract: BackgroundDespite the well-recognised health benefits of fresh fruit consumption, substantial uncertainties remain about its potential effects on incident diabetes and, among those with diabetes, on risks of death and major vascular complications.Methods and findingsBetween June 2004 and July 2008, the nationwide China Kadoorie Biobank study recruited 0.5 million adults aged 30–79 (mean 51) y from ten diverse localities across China. During ~7 y of follow-up, 9,504 new diabetes cases were recorded among 482,59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 51 publications
6
90
0
9
Order By: Relevance
“…In China, and in many parts of the world, the relative high sugar content in fresh fruit have led to diminished fruit consumption in diabetic subjects. The findings of the Chinese study suggest that fresh fruit is beneficial for primary and secondary prevention of diabetes [25]. In a large study from Brazil, it was shown that among the dietary factors they studied a low intake of fruit, (< 300 g/day), was the largest contributor to cardiometabolic deaths.…”
Section: Homa-irmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, and in many parts of the world, the relative high sugar content in fresh fruit have led to diminished fruit consumption in diabetic subjects. The findings of the Chinese study suggest that fresh fruit is beneficial for primary and secondary prevention of diabetes [25]. In a large study from Brazil, it was shown that among the dietary factors they studied a low intake of fruit, (< 300 g/day), was the largest contributor to cardiometabolic deaths.…”
Section: Homa-irmentioning
confidence: 99%
“…In a large study, with results from different parts of the world, the importance of fruit and vegetable consumption, in relation to insulin resistance and diabetes have been pointed out [24]. Another example is a prospective Chinese study, 0.5 million Chinese adults were followed during 7 years to study the effect of fruit consumption on diabetes [25]. In China, and in many parts of the world, the relative high sugar content in fresh fruit have led to diminished fruit consumption in diabetic subjects.…”
Section: Homa-irmentioning
confidence: 99%
“…Baseline data collection in CKB Information on sociodemographic status, smoking [21], alcohol drinking, physical activity [22], medical history and diet [23,24] were collected by trained health professionals using a laptop-based questionnaire. Each participant provided a 10 ml venous blood sample (with time since last eating or drinking any energycontaining food or beverage recorded).…”
Section: Study Populationmentioning
confidence: 99%
“…Poor diet, alcohol and tobacco use, low levels of PA and high levels of SB are related to obesity and cardiometabolic risk factors [2][3][4][5] , and their prevalence is high among adolescents 18 . This study found alarmingly low rates of fruit and vegetable consumption (over 70%), and high rates of alcohol (mild: 24.0%; excessive: 15.6%) and tobacco use (6.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a period characterized by significant physical and psychological changes and during which several lifelong health related behaviors are adopted and established 1 . Youth establish values, beliefs and behaviors related to eating, smoking, alcohol drinking, and physical activity, and these interact to influence risk for obesity, diabetes and other chronic condition [2][3][4][5] . The high prevalence of unhealthy behaviors in adolescence is a major public health concern due to the tendency of behaviors to track into adulthood.…”
Section: Introductionmentioning
confidence: 99%